Introducing the combined atlas framework for large‐scale web‐based data visualization: The GloNAF atlas of plant invasion. Issue 5 (22nd February 2022) - Hancock, Sebastian C.; Essl, Franz; Kraak, Menno‐Jan; Dawson, Wayne; Kreft, Holger; Pyšek, Petr; Pergl, Jan; van Kleunen, Mark; Weigelt, Patrick; Winter, Marten; Gartner, Georg; Lenzner, Bernd
Abstract: Large‐scale biodiversity data, for example, on species distribution and richness information, are being mobilized and becoming available at an increasing rate. Interactive web applications like atlases have been developed to visualize available datasets and make them accessible to a wider audience. Web mapping tools are changing rapidly, and different underlying concepts have been developed to visualize datasets at a high cartographic standard. Here, we introduce the Combined Atlas Framework for the development of interactive web atlases for ecological data visualization. We combine two existing approaches: the five stages of the user‐centred design approach for web mapping applications and the three U approach for interface success. Subsequently, we illustrate the use of this framework by developing the Atlas of Plant Invasions based on the Global Naturalized Alien Flora (GloNAF) database. This case study illustrates how the newly developed Combined Atlas Framework with a user‐centred design philosophy can generate measurable success through communication with the target user group, iterative prototyping and competitive analysis of other existing web mapping approaches. The framework is useful in creating an atlas that employs user feedback to determine usability and utility features within an interactive atlas system. Finally, this framework will enable a better‐informed development process of future visualization and dissemination of biodiversity data through web mapping applications and interactive atlases.